Affiliation motive levels in tweets from countries differentially impacted by terrorism - Quek, Min Yi (Nanyang Technological University, 2023)
Terrorist attacks could have a lasting impact on both victims and witnesses, in the form of heightened levels of distress and safety concerns. Affiliation with others has been noted to be a basic coping response in the face of threatening, uncertain or stressful circumstances, including terrorist attacks. Individuals higher in affiliation motivation are more likely to partake in social activities, initiate social contact and establish warm and friendly relations with others. Social media platforms such as Twitter have been frequently used as a means of data collection with individuals increasingly leveraging on such media to communicate and affiliate with others, as well as make sense of events. The current study thus aims to examine if tweets gathered from a country more negatively impacted by terrorism would contain higher levels of affiliation motivation compared to a country less affected by terrorism. A total of 1,398 tweets were collected from four regions — Kabul and Istalif in Afghanistan, as well as Tashkent and Dzhartash in Uzbekistan. Results suggest higher aggregate levels of need for affiliation amongst Twitter users in Afghanistan compared to those in Uzbekistan. Findings from this preliminary investigation are encouraging and reveal that affiliation motive levels differ in countries differentially impacted by terrorism, which could be a potentially useful insight for understanding post-attack recovery in communities most affected by terrorism.